Pengaruh Pengetahuan Proporsi Tubuh terhadap Hasil Belajar Menggambar Mode pada Siswa Kelas X SMK Negeri 1 Stabat - Siregar, Mutiara Jannah; Ampera, Dina (Mahesa Research Center, 2025)
This study aims to determine the effect of students' understanding of body proportions in grade X of SMK Negeri 1 Stabat on their learning outcomes in fashion drawing. This study used a Nonequivalent Control Group Design with a quasi-experimental approach. Grade X DPB 1 was designated as the experimental group, while grade X DPB 2 served as the control group and served as the sample. The research instrument used was a learning outcome assessment consisting of a pretest and posttest. The control class obtained an average pretest score of 65.88, while the experimental class obtained a score of 66.97, indicating that the initial talents of both groups were approximately equal. The average posttest score of the experimental class increased to 76.52 after being given targeted therapy on body proportions, while the control class only obtained a score of 70.59. A significant difference was shown by the results of the t-test which showed a calculated t value of 3.0263 > t table 1.6686. As a result, it can be confirmed that students' learning outcomes in drawing are positively and significantly influenced by their understanding of body proportions.